Menciptakan Harapan: Intervensi terhadap Warga Binaan (WBP) Perempuan Usia 42 tahun dalam Kasus Residivis Narkoba - Silmi Sri Rosmayanti; Fajar Utama Ritonga; Emi Triani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This practice focuses on intervention with a 42-year-old female prisoner with a drug recidivism case, specifically related to her role as a courier delivering methamphetamine. Using the mezzo intervention method introduced by Zastrow, this practice applied a social work approach with family case work methods and utilized psychodynamic models. This approach aimed to create hope and facilitate effective rehabilitation for the prisoner. The results of the practice showed that with appropriate interventions, there were improvements in emotional and behavioral aspects that could support the social reintegration process. A holistic and structured approach through family case work and in-depth understanding through the psychodynamic model played an important role in the treatment of this drug recidivist case. This finding confirms the importance of comprehensive and personalized intervention strategies in addressing drug recidivism, particularly among female prisoners.